Individual and combined in vitro (anti)androgenic effects of certain food additives and cosmetic preservatives. (April 2016) - Pop, Anca; Drugan, Tudor; Gutleb, Arno C.; Lupu, Diana; Cherfan, Julien; Loghin, Felicia; Kiss, Béla
Abstract: The individual and combined (binary mixtures) (anti)androgenic effect of butylparaben (BuPB), butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT) and propyl gallate (PG) was evaluated using the MDA-kb2 cell line. Exposing these cells to AR agonists results in the expression of the reporter gene (encoding for luciferase) and luminescence can be measured in order to monitor the activity of the reporter protein. In case of the evaluation of the anti-androgenic effect, the individual test compounds or binary mixtures were tested in the presence of a fixed concentration of a strong AR agonist (1000 pM 5-alpha-dihydrotestosterone; DHT). Cell viability was assessed using a resazurin based assay. For PG, this is the first report in the literature concerning its (anti)androgenic activity. In case of both individual and mixture testing none of the compounds or binary combinations showed androgenic activity. When tested in the presence of DHT, BuPB, BHA and BHT proved to be weak anti-androgens and this was confirmed during the evaluation of binary mixtures (BuPB + BHA, BuPB + BHT and BHA + BHT). Besides performing the in vitro testing of the binary combinations, two mathematical models (dose addition and response addition) were evaluated in terms of accuracy of prediction of the anti-androgenic effect of the selected binary mixtures. The dose addition model guaranteed a good correlation between the experimental and predicted data. However, no estimation was possible in case of mixtures containing PG, due to the lack of effect of the compound in case of the individual testing. Highlights: Certain food additives & cosmetic preservatives are potential endocrine disruptors. The selected compounds had no in vitro androgenic activity. Three of the selected compounds showed in vitro anti-androgenic activity. The effect of binary mixtures could be predicted by the dose addition model.